2016
DOI: 10.1016/j.jegh.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Disaster response under One Health in the aftermath of Nepal earthquake, 2015

Abstract: Until now, an estimate quotes that 1100 healthcare facilities were damaged and over 100,000 livestock lost in the two earthquakes that occurred in April and May of 2015 in Nepal. Threats of infectious diseases, mostly zoonoses, could affect Nepal's economy, trade, and tourism, and reaching the targets of the United Nations Millennium Development Goals. Historically, outbreaks of infectious diseases, including zoonoses, were largely associated with the aftereffects of the earthquakes. It has been documented tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
(28 reference statements)
0
19
0
1
Order By: Relevance
“…eating). The 2011 Fukushima nuclear power plant accident and the 2015 Nepal earthquake affected the agriculture sector and animal welfare, and zoonoses occurred [9,10], necessitating a cooperative approach between human Table 1. Health approach of shared environment, safe food systems, and shared medicines/interventions in the COVID-19 pandemic.…”
Section: Dear Editormentioning
confidence: 99%
“…eating). The 2011 Fukushima nuclear power plant accident and the 2015 Nepal earthquake affected the agriculture sector and animal welfare, and zoonoses occurred [9,10], necessitating a cooperative approach between human Table 1. Health approach of shared environment, safe food systems, and shared medicines/interventions in the COVID-19 pandemic.…”
Section: Dear Editormentioning
confidence: 99%
“…In order to achieve the goal of not having a major epidemic after a major disaster, we must have a profound study and learn from other countries at the same time. 45,46 Psychological Assistance Psychological problems, such as posttraumatic stress disorder, depression, and anxiety gradually became apparent in the subacute phase after the earthquake. 47,48 The results of this paper showed that the percentage of mental and behavioral disease increased significantly in the subacute phase (1.18%) compared with the acute phase (0.02%).…”
Section: Epidemic Controlmentioning
confidence: 99%
“…During the rescue and relief stage, the immediate focus is to save the lives of people, which can be done through the deployment of search-and-rescue teams (Kates and Pijawka 1977;Alexander 2007 as cited by Contreras 2016). Asokan and Vanitha (2017) emphasized the importance of a combined effort by aid agencies and health professionals in an emergency response. Further, needs assessments are vital for estimating the number of affected people from an earthquake, the number of temporary shelters required, and finally, the type of humanitarian aid required (Brown et al 2010 as cited by Contreras 2016).…”
Section: Emergency Response After An Earthquakementioning
confidence: 99%